Soft‐templating Synthesis of Mesoporous Metal–Organic Frameworks with Enhanced Toluene Adsorption Capacity. Issue 45 (5th December 2018) - Duan, Chongxiong; Yang, Minhui; Li, Feier; Li, Yanyan; Peng, Anguo; Luo, Shaojuan; Xi, Hongxia
Abstract: Metal–organic frameworks (MOFs) commonly have uniform micropores (pore dimension < 2 nm), which may restrict their practical applications involving large molecules. Although quite a little approaches have been developed to prepare mesoporous metal–organic frameworks (meso‐MOFs), challenge remains in the preparation of meso‐MOFs with controllable/tunable porosity. Here we developed a reliable method to rationally design and synthesize meso‐Cu‐BTC materials through utilizing a novel amphiphilic surfactant as the template. X‐ray diffraction, nitrogen adsorption isotherms and pore size distributions were applied to characterize the attained meso‐MOF products, the characterization analyses indicated that the as‐synthesized products possess multimodal pore size distribution with micropores and well‐ordered mesopores. Moreover, the porosity properties of the meso‐Cu‐BTC could be systematically controlled by varying the ratio of H2 O/EtOH, the amount and type of the template. Owing to the well‐order mesoporous structure, the meso‐Cu‐BTC exhibited high uptake capacity of 152 cm 3 ⋅g −1, about 20% higher as compared with conventional counterpart (128 cm 3 ⋅g −1 ) for the capture of toluene. This work provides a new strategy to prepare meso‐MOFs with tunable porosity that would fulfill a wide range of applications involving large molecules. Abstract : Synthesis of mesoporous metal–organic frameworks (MOFs) by a template strategy, the porosity properties of the mesoporous MOFs could be systematically controlled by varying the ratio of H2 O/EtOH, the amount and type of the template. The as‐synthesized mesoporous MOFs exhibited enhanced toluene adsorption capacity.